2017
DOI: 10.1007/s11239-017-1484-2
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous cardiocerebral infarction in the era of endovascular therapy: which to treat first?

Abstract: A cardiocerebral ischemic attack (CCI) or a concurrent acute ischemic stroke (AIS) and myocardial infarction (AMI) is a severe event with no clear recommendations for ideal management because of the rarity of the scenario. The narrow time window for treatment and complexity of the treatment decision puts immense pressure on the treating physician. We evaluated this challenging situation at our tertiary center. Using our prospective stroke database out of a total of 555 patients with acute ischemic stroke betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 46 publications
1
98
0
3
Order By: Relevance
“…The available evidence about this rare presentation has been mostly from reported case reports and case series. In their review paper, Yeo et al (9) reported that 6% of patients with acute stroke had ST segment elevation, but a closer look at the cited study (10) showed that none of these patients with ST segment elevations had dynamic changes consistent with evolving MI on serial electrocardiogram, nor were the creatine phosphokinase levels higher than patients without ST elevations, therefore rendering the inference of AMI incidence in the setting of acute stroke from this study unreliable. An autopsy on a patient with anterior ST elevation in setting of subarachnoid hemorrhage in this study however revealed focal areas of myocardial necrosis.…”
Section: Epidemiologymentioning
confidence: 73%
See 3 more Smart Citations
“…The available evidence about this rare presentation has been mostly from reported case reports and case series. In their review paper, Yeo et al (9) reported that 6% of patients with acute stroke had ST segment elevation, but a closer look at the cited study (10) showed that none of these patients with ST segment elevations had dynamic changes consistent with evolving MI on serial electrocardiogram, nor were the creatine phosphokinase levels higher than patients without ST elevations, therefore rendering the inference of AMI incidence in the setting of acute stroke from this study unreliable. An autopsy on a patient with anterior ST elevation in setting of subarachnoid hemorrhage in this study however revealed focal areas of myocardial necrosis.…”
Section: Epidemiologymentioning
confidence: 73%
“…An intravenous bolus of alteplase 15 mg followed by infusion of 0.75 mg/kg for 30 minutes (maximum 50 mg), then 0.5 mg/kg (maximum 35 mg) over the next 60 minutes, not to exceed a total of 100 mg can be given up to 12 hours for qualifying AMI presentations (35). The lack of a clear guideline on the unifying dose for simultaneous CCI is a source of great controversy due to the fact that studies have shown an increased risk of hemorrhagic conversion of AIS when thrombolytics are administered at higher doses (36)(37)(38), and administration of lower than recommended dose of a thrombolytic for AMI may be considered under-dosing (9).…”
Section: Management Of Simultaneous CCImentioning
confidence: 99%
See 2 more Smart Citations
“…We have presented herein a case of atrial fibrillation-associated CCI in which nearly simultaneous embolization of the cerebral and coronary arteries occurred. The term CCI was coined by Omar et al [1], and this rare condition has a reported frequency of 0.009-0.52% of ischemic strokes [7] In our case, cerebral embolism was treated first with intravenous tissue plasminogen activator (IV-tPA) and mechanical thrombectomy, followed by coronary angiography, which did not suggest any requirement for PCI. Coronary angiography suggested that alteplase at the dosage approved for ischemic stroke had resolved the coronary emboli.…”
Section: Discussionmentioning
confidence: 73%